The impact of carbon emission cap and carbon trade mechanism on the order decision with stochastic demand. (2015) - Liu, Weihua; Xie, Wenchen; Qiu, Ping
This paper mainly discusses the impact of carbon emission cap-and-trade mechanism on the order decision-making with stochastic demand. First, considering the stochastic demand, carbon emission cap-and-trade, a single-cycle order model has been established. Then this model is solved and the optimal order quantity is put forward. Many interesting observations which are different from the order decision-making for stable demand are found out. The research shows that: a value range of carbon trading price exists; carbon cap-and-trade mechanism can motivate the organisations to reduce carbon emissions effectively; whether the company should buy carbon credits depends on the actual carbon emission and carbon emission cap; reducing carbon emissions does not necessarily lead to high cost. In certain situations, companies can reduce carbon emission and total cost, increase total revenue simultaneously.